Advanced imaging techniques for small bowel Crohn's disease: what does the future hold?. (10th February 2018) - Pita, Inês; Magro, Fernando
Treatment of Crohn's disease (CD) is intrinsically reliant on imaging techniques, due to the preponderance of small bowel disease and its transmural pattern of inflammation. Ultrasound (US), computed tomography (CT) and magnetic resonance imaging (MRI) are the most widely employed imaging methods and have excellent diagnostic accuracy in most instances. Some limitations persist, perhaps the most clinically relevant being the distinction between inflammatory and fibrotic strictures. In this regard, several methodologies have recently been tested in animal models and human patients, namely US strain elastography, shear wave elastography, contrast-enhanced US, magnetization transfer MRI and contrast dynamics in standard MRI. Technical advances in each of the imaging methods may expand their indications. The addition of oral contrast to abdominal US appears to substantially improve its diagnostic capabilities compared to standard US. Ionizing dose-reduction methods in CT can decrease concern about cumulative radiation exposure in CD patients and diffusion-weighted MRI may reduce the need for gadolinium contrast. Clinical indexes of disease activity and severity are also increasingly relying on imaging scores, such as the recently developed Lémann Index. In this review we summarize some of the recent advances in small bowel CD imaging and how they might affect clinical practice in the near future.